2000
DOI: 10.1002/1522-2675(20001004)83:10<2823::aid-hlca2823>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

The First Fully Planar C 5 ‐Conformation of Homooligopeptides Prepared from a Chiral α ‐Ethylated α , α ‐Disubstituted Amino Acid: ( S )‐Butylethylglycine (=(2 S )‐2‐Amino‐2‐ethylhexanoic Acid)

Abstract: An optically active a-ethylated a,a-disubstituted amino acid, (S)-butylethylglycine ( (2S)-2-amino-2ethylhexanoic acid; (S)-Beg; (S)-2), was prepared starting from butyl ethyl ketone (1) by the Strecker method and enzymatic kinetic resolution of the racemic amino acid. Homooligopeptides containing (S)-Beg (up to hexapeptide) were synthesized by conventional solution methods. An ethyl ester was used for the protection at the C-terminus, and a trifluoroacetyl group was used for the N-terminus of the peptides. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 4 publications
3
46
0
Order By: Relevance
“…6). 32) Contrary to the planar conformation of the (S)-Beg homopeptides, the IR and 1 H-NMR spectra indicated that the dominant conformation of the heteropeptides having an (S)-Beg in the Aib sequences seemed to be the 3 10 -helical structure in CDCl 3 solution. X-Ray crystallographic analysis of CF 3 CO-{(S)-Beg}-(Aib) 4 -OEt showed both right-handed (P) and left-handed (M) 3 10 -helices, while that of CF 3 CO-(Aib) 2 -{(S)-Beg}-(Aib) 2 -OEt demonstrated a right-handed (P) 3 10 -helix.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…6). 32) Contrary to the planar conformation of the (S)-Beg homopeptides, the IR and 1 H-NMR spectra indicated that the dominant conformation of the heteropeptides having an (S)-Beg in the Aib sequences seemed to be the 3 10 -helical structure in CDCl 3 solution. X-Ray crystallographic analysis of CF 3 CO-{(S)-Beg}-(Aib) 4 -OEt showed both right-handed (P) and left-handed (M) 3 10 -helices, while that of CF 3 CO-(Aib) 2 -{(S)-Beg}-(Aib) 2 -OEt demonstrated a right-handed (P) 3 10 -helix.…”
mentioning
confidence: 82%
“…The author prepared homopeptides composed of (S)-Beg; CF 3 CO-{(S)-Beg} n -OEt (nϭ1-6), 32) and heteropeptides containing an (S)-Beg in Aib sequences; CF 3 CO-{(S)-Beg}-(Aib) 4 -OEt, and CF 3 CO-(Aib) 2 -{(S)-Beg}-(Aib) 2 -OEt and studied the preferred secondary structures. 33,34) The IR spectra of (S)-Beg homopeptides showed intramolecularly hydrogen-bonded weak N-H absorption [C-F · · · H(N) · · · OϭC of the N-terminus] at 3380-3415 cm…”
Section: Secondary Structure Of Peptides Composed Of Chiral a A-ethylmentioning
confidence: 99%
“…We have studied the conformation of peptides prepared from the chiral a-ethylated a,a-disubstituted amino acid (S)-butylethylglycine ((S)-Beg), and reported that (S)-Beg homopeptides form the fully planar C 5 conformers [8], and that heteropeptides containing an (S)-Beg within a sequence of Aib adopt the 3 10 -helical structure both in solution and in the solid state [9]. In this paper, we describe the synthesis of heteropeptides containing the chiral a-ethylated a,a-disubstituted a-amino acid (S)-aethylleucine ( (S)-isobutylethylglycine (2S)-2-amino-2-ethyl-4-methylpentanoic acid; (S)-aEtLeu) within sequences of Aib residues and Deg residues, and their conformational analyses 1 ).…”
mentioning
confidence: 99%
“…After deprotection of the CF 3 CO group in 9 by NaBH 4 reduction, the coupling of the amine obtained and the acid 6 was attempted with EDC in refluxing MeCN. Unfortunately, no tripeptide 10 was isolated because of the steric hindrance of aEtLeu [8].…”
mentioning
confidence: 99%
“…[18][19][20] In contrast, peptides composed of acyclic dAAs with two bulky substituents equal to or larger than ethyl groups are more likely to form extended planar C5 conformations. 4,[21][22][23][24][25] Therefore, the side chains of dAAs in peptides change from a cyclic to an acyclic structure with two bulky substituents, as a consequence, peptide secondary structures may change from a helical to a planar or random structure. In the present study, we designed dAAs with a cyclic acetalside chain.…”
mentioning
confidence: 99%